SYVN1-MTR4-MAT2A Signaling Axis Regulates Methionine Metabolism in Glioma Cells - Wang, Lude; Hu, Bin; Pan, Kailing; Chang, Jie; Zhao, Xiaoya; Chen, Lin; Lin, Haiping; Wang, Jing; Zhou, Gezhi; Xu, Wenxia; Yuan, Jianlie (Frontiers in Cell and Developmental Biology, 2021)
Methionine is one of the essential amino acids. In methionine-restriction environment, how tumor cells adapt and adjust signal transduction network to avoid the apoptosis fate is a scientific problem worthy of further exploration. In this study, we mainly studied the molecular mechanism of glioma response to methionine-restriction environment, providing a theoretical basis for seeking new treatment strategies for glioma. Methods: Here, we constructed methionine-restriction tolerance cells in order to study the glioma response to methionine-restriction environment. The transcriptome analysis of the tolerant cells showed significant changes in MAT2A.Western blot, Immunohistochemistry, qRT-PCR, clone formation and other experiments were used to verify the role of MAT2A in glioma genesis. In addition, the regulation mechanism of MAT2A mRNA nuclear export was investigated by transfection, plasma nucleation separation and co-immunoprecipitation. Results: When glioma cells responded to methionine restriction, the expression of MAT2A was high, and the inhibitor of MAT2A inhibited the proliferation of tumor cells. The expression of MAT2A was positively correlated with WHO grade of glioma. The high expression of MAT2A is related to the increase of its mRNA out of the nucleus, The expression of nuclear export regulatory molecule MTR4 can affect the export of MAT2A mRNA. In a methionine-restriction environment, the ubiquitination of MTR4 was enhanced and thus the protein level was reduced, and the E3 ubiquitin ligase was verified to be SYVN1. Conclusions: In summary, methionine restriction leads to increased ubiquitination of MTR4, which promotes MAT2A mRNA out of the nucleus and MAT2A protein expression. MAT2A promotes histone methylation to prompt cells to proliferate in a methionine- restriction environment.